1993
DOI: 10.1038/364737d0
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Single-shell carbon nanotubes of 1-nm diameter

Abstract: ACKNOWLEDGEMENTS. We thank G. Frey for M. kandleri cells, L. Liu for antibody aga inst human topoisomerase I, H. Nash for). Int protein , Y. C. Tse-Dinh for E. coli topoisomerase I. J. Wang tor S. cerevisiae topoisomerase Ill and antibody against E. coif topoisomerase I, and C. Scheim er and K Eichinger for technical assistance. The work was supported in part by funds from the Leibniz Preis (K.S.) and the NSF (JAL.), and by Alexa nder von Humboldt and Alfred P. Sloan fellowships (to A.LS.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 0 publications
0
62
0
1
Order By: Relevance
“…Surprisingly, despite their very similar chemical and electronic structure -CNTs are essentially 'rolled up' GNRs 17,18,19 -ultrafast photoconductivity measurements performed on both CNTs 20,21 and GNRs 22 have led to varying conclusions on the primary photoproducts. Xu et al 21 found that the photoresponse of isolated CNTs was dominated by electrons and holes tightly bound in excitons.…”
Section: Toc Graphicmentioning
confidence: 99%
“…Surprisingly, despite their very similar chemical and electronic structure -CNTs are essentially 'rolled up' GNRs 17,18,19 -ultrafast photoconductivity measurements performed on both CNTs 20,21 and GNRs 22 have led to varying conclusions on the primary photoproducts. Xu et al 21 found that the photoresponse of isolated CNTs was dominated by electrons and holes tightly bound in excitons.…”
Section: Toc Graphicmentioning
confidence: 99%
“…In addition, Stacked-Cup Carbon Nanotubes (SCCNTs) or Carbon Nanotube-Fibers (CNTFs) have unique structures with highly graphitic as shown in figure 1. The graphene planes in the structures of (SCCNTs) or (CNTFs) are canted from the fiber axis, resulting in exposed edge plane on the interior and exterior surfaces of the fiber; CNTs, on the other hand, typically resemble an assembly of concentric cylinders of graphene [7][8][9] Fowler-Nordheim (FN) first derived a semiclassical theory of FE based on physical assumptions and mathematical approaches; the theory has been modified many times over years to describe Cold Field Emission (CFE) from bulk metal where it is known as Fowler-Nordheim (FN) equation which is given by [10,11]:…”
Section: Introductionmentioning
confidence: 99%
“…One of the carbon nanotube applications is using them as nanocomposite materials [12]. Nanotubes are divided into two categories: single-walled (SWNT) and multi-walled (MWNT); and CNTs are classified into three groups on some articles, such as SWNTs (single-walled carbon nanotubes) [13,14], DWNTs (double-walled carbon nanotubes) [15], and MWNTs (multi-walled carbon nanotubes) [16]. All nanotubes have shown high tensile strength [8,17], and excellent mechanical properties [16], therefore, carbon nanotubes can also be used as polymer's reinforcing agents; CNTs can be used as a filler for polymer nanocomposites [15].…”
Section: Introductionmentioning
confidence: 99%